ANALISIS YURIDIS TERHADAP PEMBOBOLAN DANA NASABAH CITIBANK DALAM PERSPEKTIF UNDANG-UNDANG PERBANKAN DAN UNDANG-UNDANG TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - HERRY FEBRIAN; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
Citibank is a multinational bank that operated in Indonesia. Citibank is a part of Citigroup where its shares listed in New York Stock Exchange (NYSE). The case of Citibank was occurred and exposed on March of 2011 when a Citibank receive the complaint of three customer related to the loss of their fund in saving, the Citibank report the case to the police. Based on investigation indicates that there is hit of the fund of customer by the senior employee in position as vice president in the bank whose name Melinda Dee. The hit of the fund involves the employee of Citibank as teller. In this research, the problem is formulated as follows : to study the position of customer as consumer of banking product, to study the juridical analysis of fund hit of the customer of Citibank in the perspective of Banking Act and the Act of eradication and prevention of Money Laundry and to study the protection of customer on the fund hit of customer of Citibank. The banking business is a trust business. So the case of fund hit of the customer can not be neglected even the hit of fund is conducted by a staff of the bank if the trust of the consumer to the banking make not lost. In the view point of law how to prevent the reoccurrence of the case or be minimized by the Act No. 10 of 1998 concerning to the Banking and Act No. 8 of 2010 concerning to Prevention of Money Laundry. In order to anticipate the hit of fund in Citibank and in other banks in Indonesia and the prevention of money laundry in Indonesia, it is suggested to the law enforcer to punish the severe punishment to the evil doer generally and to the hitter of the fund of the customer of Citibank especially because this condition will provide them with the wary effect to the evil doer and to recover the trust of customer to the banks and the law enforcer in Indonesia. Keywords : Bank, Customer, Money Laundry